Electrocatalytic performance of Pt–Ni nanoparticles supported on an activated graphite electrode for ethanol and 2-propanol oxidation. Issue 61 (7th October 2020) - Chelaghmia, M. L.; Nacef, M.; Fisli, H.; Affoune, A. M.; Pontié, M.; Makhlouf, A.; Derabla, T.; Khelifi, O.; Aissat, F.
Abstract : Platinum (Pt) and platinum–nickel (Pt–Ni) electrocatalysts were prepared on activated graphite electrodes by an electrochemical deposition process. Abstract : Platinum (Pt) and platinum–nickel (Pt–Ni) electrocatalysts were prepared on activated graphite electrodes by an electrochemical deposition process. The electrocatalysts were analyzed by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). The electrocatalytic activity of the prepared electrocatalysts, their stability, and the effect of temperature toward ethanol and 2-propanol oxidation were evaluated by cyclic voltammetry (CV), chronoamperometry and electrochemical impedance spectroscopy (EIS). The results showed that the Pt–Ni/C exhibited higher catalytic activity, better stability and better tolerance to poisoning by ethanol and 2-propanol oxidation intermediate species compared to Pt/C, which was interpreted as synergistic and electronic effects between Pt and Ni. A study of the temperature dependence of ethanol and 2-propanol oxidation in the temperature range of 298–318 K, shows that the apparent activation energy for ethanol and 2-propanol oxidation on Pt–Ni/C was lower than on Pt/C. The results also revealed that the electro-oxidation of ethanol and 2-propanol on Pt/C were improved by raising the temperature and Ni modification.